2015
DOI: 10.1088/2053-1583/2/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Graphene coatings for chemotherapy: avoiding silver-mediated degradation

Abstract: Chemotherapy treatment usually involves the delivery of fluorouracil (5-Fu) together with other drugs through central venous catheters. Catheters and their connectors are increasingly treated with silver or argentic alloys/compounds. Complications arising from broken catheters are common, leading to additional su↵ering for patients and increased medical costs. Here, we uncover a likely cause of such failure through a study of the surface chemistry relevant to chemotherapy drug delivery, i.e. between 5-Fu and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…With a small energy difference, H and F atoms can be liberated from 5-Fu and evaporate as HF ( Fig. 2(c)), giving the same reaction products as reported previously [1], with the same energy, but with the important difference that the intermediate steps (with H and F bonded to the Ag substrate) are not required. We also identify two dimer products; Fig.…”
Section: Reactionsupporting
confidence: 62%
See 2 more Smart Citations
“…With a small energy difference, H and F atoms can be liberated from 5-Fu and evaporate as HF ( Fig. 2(c)), giving the same reaction products as reported previously [1], with the same energy, but with the important difference that the intermediate steps (with H and F bonded to the Ag substrate) are not required. We also identify two dimer products; Fig.…”
Section: Reactionsupporting
confidence: 62%
“…We therefore investigate alternative reaction pathways in which these intermediate steps are not required. Several such pathways exist, but they involve more than one 5-Fu molecule; In the bulk crystal structure of 5-Fu, the molecule-molecule attraction is dominated by hydrogen bonding between an H atom of one molecule and the F atom of a neighbouring molecule [14] -and a similar ordering (and therefore H to F attraction) has been reported for thin films on Ag(111) [1]. It is therefore possible that the H to F attraction could lead to reactions between neighbouring 5-Fu molecules.…”
Section: Reactionmentioning
confidence: 75%
See 1 more Smart Citation
“…Graphene had been used as an alternative coating for catheters to improve the delivery of chemotherapy drugs. The research suggested that placing graphene which is an extremely thin sheet of carbon atoms; on the internal surfaces of intravenous catheters commonly used to deliver chemotherapy drugs into a patient's body will improve the efficacy of treatments, and reduce the potential of the catheters breaking [14]. The study indicates that damaging interactions can occur between the most commonly used chemotherapy drugs, 5-Fluorouracil (5-Fu) and silver-one of the most widely used coating materials in medical applications.…”
Section: Improving the Delivery Of Chemotherapymentioning
confidence: 99%
“…An extreme example of surface migration causing corrosion resistance is the formation of graphene from bulk impurities on a range of reactive metal surfaces 11,12 , giving rise to a single-atom-thick inert and corrosion resistant coating with a broad range of potential applications 13,14 . It is therefore interesting to understand which bulk species agents migrate towards the surface and/or grain boundaries of the material and the thermal dependency of these mechanisms.…”
mentioning
confidence: 99%